2015
DOI: 10.1111/pan.12790
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone version of the Faces Pain Scale‐Revised and the Color Analog Scale for postoperative pain assessment in children

Abstract: The Panda smartphone application can be used in lieu of the original FPS-R and CAS for assessment of pain in children. Children's preference for Panda may translate to improved cooperation with self-report of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 29 publications
3
44
1
3
Order By: Relevance
“…Nevertheless, there is no consensus on the ideal time interval between PRO administrations when carrying out test–retest validation: intervals have ranged from 1 min to 7 years . Other studies have also used 30 min as a washout period . In order to reduce patient time and travel burden, as well as to ensure disease severity did not fluctuate between administrations, the shorter washout period of 30 min was used.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no consensus on the ideal time interval between PRO administrations when carrying out test–retest validation: intervals have ranged from 1 min to 7 years . Other studies have also used 30 min as a washout period . In order to reduce patient time and travel burden, as well as to ensure disease severity did not fluctuate between administrations, the shorter washout period of 30 min was used.…”
Section: Discussionmentioning
confidence: 99%
“…The app incorporated digital self‐report pain scales designed for use with children: the Faces Pain Scale Revised (FPS‐R) for children aged 4 years and older and the Color Analogue Scale (CAS) for children aged 5 years and older . Good agreement between the digital and the original paper‐based versions of the FPS‐R and CAS on a mobile device have previously been shown; the digital versions were preferred by children . The app also incorporated two simplified pain scales, designed and evaluated by our team, which may be more appropriate for self‐report assessments of pain in younger children (4 years of age): the Simplified Faces Pain Scale (S‐FPS) and Simplified Concrete Ordinal Scale (S‐COS) …”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, we have developed a prototype smartphone app called Panda , designed to aid parents/guardians in assessing postoperative pain and managing analgesic medications at home. The app includes pediatric pain scales, scheduling of reminder notifications for pain assessments and medication administration, and tracking of the resulting pain scores and administered medication. The aims of this study were to evaluate the usability and feasibility of the Panda app.…”
Section: Introductionmentioning
confidence: 99%
“…Terri et al found electronic versions of the Faces Pain Scale-Revised (FPS-R) and the Color Analog Scale (CAS) on a smartphone demonstrated good agreement with the original paper and plastic versions of these scales. [41]. Pawar et al found Software version of Roland Morris Disability questionnaire was comparable to the paper version in patients with low back pain [42].…”
Section: Discussionmentioning
confidence: 99%